Ultraviolet-C decontamination of a dental clinic setting: required amount of UV light - Botta, Sergio Brossi; Teixeira, Fernanda de Sá; Hanashiro, Fernando Seishim; Araújo, Wagner Wlysses Rodrigues de; Cassoni, Alessandra; Salvadori, Maria Cecilia Barbosa da Silveira (Brazilian Dental Science, 2020)
Abstract Viruses can spread to the environment, and it can be challenging to clear it. A direct approach to limit airborne transmission of pathogens in dental clinic offices is to inactivate viruses within a short time of their production and block the person-to-person transmission routes in dental clinics. For this, we can use chemical substances on surfaces and germicidal ultraviolet light (UV), typically at 254 nm, for complementary disinfection of surfaces and air contaminated by aerosols produced by high-speed handpiece or ultrasound scaler. Based on the literature review and the similarity of Sars-Cov-2 with other previously studied corovaviruses, COVID-19 is sensitive to UV irradiation that can break the genome of this virus, inactivating it. In our study, we performed the calculation of the time required to decontaminate a dental care room between each patient change. We can conclude that the use of UVC can be incorporated into the dental care routine to reduce cross contamination. Keywords UVC-decontamination; Sterilization; Ultraviolet light; Dentistry; Sars-Cov-2.